Circadian pattern of intragastric acidity in duodenal ulcer patients: a study of variations in relation to ulcer activity. Issue 10 (October 1991) - Wagner, S; Gladziwa, U; Gebel, M; Schüler, A; Freise, J; Schmidt, F W
Abstract : The relation between intragastric acidity and duodenal ulcer activity was studied prospectively in 21 patients with endoscopically proved duodenal ulcers. The 24 hour intragastric acidity was measured on four separate occasions by continuous recording using combined glass electrodes: (a) in the presence of an ulcer crater without treatment; (b) during active ulceration being treated with ranitidine; (c) during early healing after a six week course of ranitidine; (d) during late healing six months after acute ulceration. Intragastric acidity was also monitored in 20 healthy subjects. At all stages of ulcer activity and during all predefined time periods, duodenal ulcer patients had significantly higher gastric acidity than healthy control subjects. Duodenal ulcer patients showed a similar circadian pattern of intragastric acidity during exacerbation of ulcer disease and in remission during the early and late ulcer healing periods. These results argue against a direct relation between the activity of duodenal ulcer disease and gastric acidity. It is concluded that the chronic recurrent course of duodenal ulcer disease does not result from a fluctuation in intragastric acidity.